Relationship between mothers’ weight gain during pregnancy, neonatal birth ‎weight and cesarean cases in villages and cities - maryam asgharnia; ziba zahiri; zivar kashoofi (Journal of Holistic Nursing and Midwifery, 2005)
Introduction: The goal of prenatal care is maintenance of mother health and delivery of a ‎healthy neonate. Weight gain is the most obvious physical change during pregnancy and ‎controlling mother weight plays an important role in safe process of pregnancy.‎